Autophagy and synaptic plasticity: epigenetic regulation - Hwang, Jee-Yeon (Curr Opin Neurobiol, 2019)
In neurons, autophagy is crucial to proper axon guidance, vesicular release, dendritic spine architecture, spine pruning and synaptic plasticity and, when dysregulated, is associated with brain disorders, including autism spectrum disorders, and neurodegenerative diseases such as Parkinson’s and Alzheimer’s disease. Once thought to play a housekeeping function of removing misfolded proteins or compromised organelles, neuronal autophagy is now regarded as a finely tuned, real time surveillance and clearance system crucial to synaptic integrity and function. Here we review the role of autophagy in synaptic plasticity and its regulation by epigenetic mechanisms.